2012
DOI: 10.5398/medpet.2012.35.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adaptation and Biomass Production of Macroptilium bracteatum Inoculated with AMF in Drought Condition

Abstract: The objective of this experiment was to evaluate the effect of drought stress and mycorrhizal inoculation on physiological adaptation and biomass production of Macroptilium bracteatum. This experiment was arranged in completely randomized design with four treatments: M0 (no AM + watered), M1 (AM + watered), M2 (no AM + drought), and M3 (AM + drought) with three replicates. The observed variables were soil water content, leaf water potential, leaf relative water content, leaf proline, leaf water soluble carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…The roles of Arbuscular mycorrhizal fungi in acid soil can enhance the supply and absorbtion of P nutrient which is generally very low in this land such as N (NH 4 + or NO 3 -), K and Mg, and also can enhance micro nutrient absorption in acid soil such as Cu, Zn, Mn, B, and Mo (Smith & Read, 2008). The symbiosis of plant and AMF is known as a biological fertilizer because it can help the plant to enhance the uptake of nutrient such as P, increase disease resistence, and water relations (Smith & Read, 2008;Karti et al 2012, Sowmen et al, 2012. The AMF inoculation significantly increases the production of herbage, dry weight of shoot, and nutrient status (P, Zn, and Fe) compared to non-inoculated plants (Chaudhary et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of Arbuscular mycorrhizal fungi in acid soil can enhance the supply and absorbtion of P nutrient which is generally very low in this land such as N (NH 4 + or NO 3 -), K and Mg, and also can enhance micro nutrient absorption in acid soil such as Cu, Zn, Mn, B, and Mo (Smith & Read, 2008). The symbiosis of plant and AMF is known as a biological fertilizer because it can help the plant to enhance the uptake of nutrient such as P, increase disease resistence, and water relations (Smith & Read, 2008;Karti et al 2012, Sowmen et al, 2012. The AMF inoculation significantly increases the production of herbage, dry weight of shoot, and nutrient status (P, Zn, and Fe) compared to non-inoculated plants (Chaudhary et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Roots infected by AMF have hyphae that can absorb water more efficient, so that the plant will be tolerant and can grow on dried condition. Karti et al (2012) and Sowmen et al (2012) reported that AMF application during drought condition could improve relative water contents of leaves in Stylosanthes seabrana and Macroptillium bracteatum. The AMF can be used as an alternative strategy to substitute half of fertil-izer utilization for plant especially for plants grown in the drought condition.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan pola penanganan yang serupa terhadap lingkungan tumbuh suboptimal, Panca Dewi Manu Hara Karti memulai dengan penelitian disertasi pada tanaman pakan ternak. Karti et al (2012) mempelajari mekanisme toleransi Setaria splendida terhadap keracunan Al dan peranan mikroorganisme tanah dalam meningkatkan kelarutan fosfat tanah. Pada berbagai penelitian lanjutan telah dilakukan penelitian guna pengembangan teknologi produksi pada kondisi lingkungan cekaman kekeringan, meliputi :…”
Section: Pemanfaatan Sda Mikroorganisme Tanahunclassified
“…2. Peranan FMA dalam meningkatkan produktivitas, kualitas nutrisi, dan mekanisme toleransi terhadap kekeringan pada Stylosanthes seabrana, (Karti et al 2012) 3. Adaptasi legum pohon Macropthilium bracteatum yang diinokulasi dengan fungi mikoriza arbuskular (FMA) saat cekaman kekeringan (Sowmen et al 2014) 4.…”
Section: Pemanfaatan Sda Mikroorganisme Tanahunclassified
See 1 more Smart Citation